Changes in lucerne pollinating wild bee assemblages in Hungary from the pre-pesticide era to 2007. - Tanács, Lajos; Benedek, Pál; Móczár, László (Contributions to Entomology = Beiträge zur Entomologie, 2009)
As a result of five national surveys in Hungary from the pre-pesticide era up to recent years (1954-1956, 1967-1968, 1971-1972, 1998-2002, 2003-2007), rich wild bee assemblages were recorded at flowering lucerne fields. 196 bee species were detected, including the honey bee. Comparing the structure of wild bee assemblages visiting flowering lucerne fields in Hungary, it can be concluded that their species composition changed considerably in this period of rather more than fifty years. First, a dramatic decline of Eucera and Tetralonia species of medium flight periods was detected from the pre-pesticide era (1954-1956) up to the pesticide era in Hungary (1967-1968). This situation remained unchanged up to the present time. The main reason for this is the more widespread use of herbicides on arable land, as well as mechanical weed control becoming a regular practice along roadsides, ditches and in fields of cultivated crops. The decline of non-cultivated ruderal plots in cultivated crop fields and nearly-natural areas at the expense of more intense agricultural land use are also responsible for the considerable changes in the composition of wild bee assemblages. At the same time, the ratio of some mid summer wild bee species of short flight period increased considerably (Melitta leporina (Pz.), Rhophitoides canus Ev.) from the fifties up to the late sixties, because the acreage of lucerne production increased in this period and the size of individual lucerne fields was greatly enlarged, providing greater pollen resources and nesting possibilities for these specialist bees. This tendency, however, reversed in the past decade because lucerne production greatly decreased as a result of a greatly reduced demand for fodder legumes in Hungary. In recent years a new trend seems to have arisen, with a rapid increase in the dominance of bumble bees (Bombus species) and accompanying reduction in abundance of other groups of wild bee. Keywords wild bees, changing dominance, effect of changing agriculture.